PTU-051 Iatrogenic Hypokalaemia in Acute Severe Colitis. (17th August 2016) - Harrington, C; Smith, L; Munro, J; Laird, S; Cahill, A; Gaya, D; Morris, A; Winter, J
Abstract : Introduction: Intravenous corticosteroids have been established as the mainstay treatment of acute severe colitis since 1974. 1 BSG and ECCO guidelines advise either IV hydrocortisone 100 mg qds or IV methylprednisolone 30 mg bd in this setting. 2, 3 The potent mineralocorticoid effect of hydrocortisone however is well known. 4 This could predispose to hypokalaemia in this susceptible patient cohort. For this reason, we have recently changed our practice at Glasgow Royal Infirmary (GRI) to treat these patients with methylprednisolone. Methods: We performed a retrospective review of electronically held records of patients who presented to GRI with acute severe colitis treated with IV hydrocortisone or methylprednisolone. We collected data on the duration of treatment, potassium level on presentation, nadir potassium level, fall in potassium level and potassium replacement per patient. Results: 20 patients were treated with IV hydrocortisone for a median of 6 days, and 16 patients were treated with IV methylprednisolone for a median of 5.5 days (ns). Median serum potassium concentration on admission was 3.8 mol/l (IQR 3.4–4.1 mmol/l) in the cohort receiving hydrocortisone which was not significantly different from 4.1 mmol/l (IQR 3.7–4.1 mol/l) in the cohort receiving methylprednisolone. Following IV steroids, median nadir potassium concentration in the group receiving methylprednisolone was 3.75 mmol/l (IQR 3.5–4.1 mmol/l), not significantly different to pre-treatment values. In those receiving hydrocortisone however, potassium concentration fell by a median of 0.85 mol/l (IQR 0.2–1.1 mol/l) to a nadir of 3.1 mol/l (IQR 2.8–3.3 mol/l), significantly lower than the group receiving methylprednisolone (p < 0.0001). Only 3/16 (19%) patients receiving methylprednisolone needed potassium supplementation (2 oral and one IV). In contrast only 2/20 patients receiving hydrocortisone did not require potassium supplementation, with 10/20 (50%) requiring a median of 80 mmoles of IV potassium chloride (IQR 55–196 mmoles) and 8/20 (40%) requiring oral supplementation. 2 patients receiving hydrocortisone experienced severe hypokalaemia with ECG changes requiring management in the coronary care unit. Conclusion: Hypokalaemia is a common occurrence in patients with acute severe colitis treated with IV hydrocortisone but is rare when methylprednisolone is used. Given that both drugs are considered to be equally effective, methylprednisolone appears to be a safer choice of corticosteroid. References: 1 Truelove SC, Jewell DP. Intensive intravenous regimen for severe attacks of ulcerative colitis. Lancet 1974;1 :1067–1070. 2 BSG Guidelines for management IBD 2011. 3 ECCO consensus guidelines for UC 2012. 4 Ramsahoye BH, Davies SV, et al . The mineralocorticoid effects of high dose hydrocortisone. BMJ 1995;310 :656. Disclosure of Interest: None Declared